Green infrastructure for landscape planning : integrating human and natural systems - Austin, Gary (Gary D.) (London : Routledge, 2014)
Green infrastructure integrates human and natural systems through a network of corridors and spaces in mixed-use and urban settings. Gary Austin takes a broad look at green infrastructure concepts, research and case studies to provide the student and professional with processes, criteria and data to support planning, design and implementation.
Includes bibliographical references and index.
Keywords: Urban ecology (Sociology).; City planning -- Environmental aspects; Environmental engineering; Municipal engineering; Ecological landscape design; Sustainable urban development